2021
DOI: 10.3390/land10030278
|View full text |Cite
|
Sign up to set email alerts
|

Building Agroforestry Policy Bottom-Up: Knowledge of Czech Farmers on Trees in Farmland

Abstract: Czech agriculture is dealing with the consequences of climate change. Agroforestry cultures are being discursively reintroduced for better adaptability and resilience, with the first practical explorations seen in the field. Scholars have been working with farmers and regional stakeholders to establish a baseline for making agroforestry policy viable and sustainable. In a research effort that lasted three years, a large group of Czech farmers was interviewed via questionnaire surveys, standardized focus groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The establishment and maintenance of new agroforestry systems can face several challenges. The results of focus-group discussions and surveys of farmers (landowners and land managers) across Europe indicated that excessive bureaucratization, high costs of establishment, uncertain profitability, lack of knowledge, practical demonstrations, recommendations for establishment and management, and lack of state support systems, as well as some skepticism and negative prejudices, are severe concerns among farmers [79][80][81][82][83]. Furthermore, in Latvia and other EU countries, the implementation of agroforestry systems on agricultural land is hindered by current legislation.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment and maintenance of new agroforestry systems can face several challenges. The results of focus-group discussions and surveys of farmers (landowners and land managers) across Europe indicated that excessive bureaucratization, high costs of establishment, uncertain profitability, lack of knowledge, practical demonstrations, recommendations for establishment and management, and lack of state support systems, as well as some skepticism and negative prejudices, are severe concerns among farmers [79][80][81][82][83]. Furthermore, in Latvia and other EU countries, the implementation of agroforestry systems on agricultural land is hindered by current legislation.…”
Section: Discussionmentioning
confidence: 99%
“…Creating diverse and interconnected ecosystems contributes to biodiversity conservation and supports the preservation of valuable ecological services. Moreover, agroforestry allows farmers to diversify their income streams and improve economic stability by introducing a broader range of products and valueadded opportunities [144].…”
Section: S-sustainable Agriculture Agroforestry and Bioeconomymentioning
confidence: 99%
“…Each introduced the socio-economic and environmental benefits of AF, particularities of tree establishment and management, and to the current (limited) possibilities of growing trees on agricultural land in the Czech Republic. A semi-structured interview script was followed (see [32] for full details).…”
Section: Farmers' Perception Of Agroforestrymentioning
confidence: 99%
“…The absence of practical examples or demonstrations of AF farms in the Czech Republic, together with the inexistence of support in the form of training materials and advisory service, deepens farmers' concerns based on the established stereotypes: (i) geographical-AF is not suitable for temperate climate; (ii) ecological-woody vegetation has always been considered as an 'enemy' of modern farming due to the tree-crop competition and obstacles for mechanization; (iii) social-farmers view themselves as producers of crops or animals, and growing trees will lead to the marginalization of farming; (iv) economicaltrees cultivated on fields do not pay-off economically; and (v) political-it is a tool to get agriculture under the control of officials. The detailed results of the FG discussions are presented in [32].…”
Section: The Farmers' Perceptions Of Agroforestrymentioning
confidence: 99%